Pengaruh Likuiditas, Leverage Dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan - Eka Setiawati; Ai Hendrani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Profitability needs to be considered as a determinant of good and bad of a company in obtaining profits, Management can use profitability as a strategy to help maximize company profits. This study aims to identify factors affecting the profitability of companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) from 2020-2022. Using causality design and using purposive sampling method to collect 108 financial statement data from 36 companies, this research model uses panel data regression analysis. The results of the study show that liquidity (CR), leverage (DER) and company size have a positive and significant impact on profitability (ROA), while liquidity (CR) has a significant negative impact on profitability (ROA), leverage (DER) has a significant negative impact on profitability (ROA) and company size has no impact on profitability (ROA). Keywords: Profitability, Liquidity, Leverage, Firm Size